2019
DOI: 10.2174/1874285801913010241
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antifungal Susceptibility, Virulence Genes and Biofilm Formation in Candida albicans

Abstract: Background: Candida albicans has emerged as an important nosocomial pathogen. The morbidity and mortality associated with this pathogen are related to the presence of virulence genes and antifungal resistance. The objective of the present study was to investigate the prevalence of antifungal resistance, biofilm formation and some virulence genes such as ALS1, PLB1, INT1, SAP1 and HWP1, among clinical isolates of Candida albicans recovered from immunocompromised pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Moreover, Shrief et al in Mansoura, Egypt revealed that the biofilm capacity was identified by the microplate method in 58% of C. albicans isolated from ICU patients with nosocomial infections. The OD was intense in 20 isolates, moderate in 21 isolates and mild in 17 isolates [26]. Similarly, İnci et al in Turkey reported that the slime factor was found to be positive in 34.5% of C. albicans isolates when using the microplate test that 43% of the C. albicans isolates from oral mucosa were capable of forming biofilm using the MTT assay [14].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, Shrief et al in Mansoura, Egypt revealed that the biofilm capacity was identified by the microplate method in 58% of C. albicans isolated from ICU patients with nosocomial infections. The OD was intense in 20 isolates, moderate in 21 isolates and mild in 17 isolates [26]. Similarly, İnci et al in Turkey reported that the slime factor was found to be positive in 34.5% of C. albicans isolates when using the microplate test that 43% of the C. albicans isolates from oral mucosa were capable of forming biofilm using the MTT assay [14].…”
Section: Discussionmentioning
confidence: 88%
“…Shrief et al reported a frequency of 77% for the HWP1 gene and BioMed Research International 65% for the ALS1 gene of C. albicans isolated from blood and urine cultures. They also described that 58% of C. albicans were capable of biofilm production [48]. The prevalence of the ALS1 and HWP1 genes was detected in 48% and 3.9% of the strains isolated from vaginal samples in Turkish women, respectively [49].…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, the biofilm capacity was observed in 58% of Candida albicans isolates from the chemotherapy patients. Also, the prevalence of ALS1 and HWP1 genes among the biofilmpositive C. albicans was 56.9% [48]. Inci et al showed the presence of ALS1 and HWP1 genes in 83.1% and 11.3%, respectively, of biofilm-producing isolates [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the literature, normal flora can affect the health of the host by altering into a pathogenic organism [3]. Pathogenic species possess virulence factors that are associated with enhancing pathogenicity and resisting harsh conditions such as the implication of biofilm resulting in the resistance of yeasts to antifungal drugs [42,43].…”
Section: Discussionmentioning
confidence: 99%